The benefits of spaceflight and space exploration - Porterfield, Jason (From Earth to the stars., 2018)
Explores the technology developed for spaceflight and space exploration and the discoveries made as a result. Discusses how these developments and discoveries have impacted everyday life, such as satellite television, the ability to track climate change, digital cameras and smartphones, and our understanding of the universe. Includes sidebars, a glossary, and resources for further information.